Model Matematika SEIRS-SEI Penyebaran Penyakit Leptospirosis dengan Pengaruh Curah Hujan - Arsiyandi, Ashraff; Rosha, Media (UNIVERSITAS NEGERI PADANG, 2024)
Leptospirosis is an illness spread from animals to humans brought on by Leptospira sp. This illness is widespread and can be found anywhere there is human habitation, although it is notably prevalent in the rainy Southeast Asian countries. The goal of this modelling is to analyse the results of mathematical models of the spread of leptospirosis illness under the effect of rainfall and to understand the implications of those results. This study offers a theoretical analysis of a fundamental problem in epidemiology: the spread of leptospirosis in response to rainfall. This study shows that rainfall has a significant impact on leptospirosis rates. The analysis of fundamental reproductive value demonstrates this effect, showing that an increase in rainfall leads to an epidemic of leptospirosis.